Induction of Arabidopsis defense genes by virulent and avirulent Pseudomonas syringae strains and by a cloned avirulence gene. - Dong, X (1991)
We developed a model system to study the signal transduction pathways leading to the activation of Arabidopsis thaliana genes involved in the defense against pathogen attack. Here we describe the identification and characterization of virulent and avirulent Pseudomonas syringae strains that elicit disease or resistance symptoms when infiltrated into Arabidopsis leaves. The virulent and avirulent strains were characterized by determining growth of the pathogen in Arabidopsis leaves and by measuring accumulation of mRNA corresponding to Arabidopsis phenylalanine ammonia-lyase (PAL), beta-1,3-glucanase (BG), and chalcone synthase (CHS) genes in infected leaves. The virulent strain, P. syringae pv maculicola ES4326, multiplied 10(5)-fold in Arabidopsis leaves and strongly elicited BG1, BG2, and BG3 mRNA accumulation but had only a modest effect on PAL mRNA accumulation. In contrast, the avirulent strain, P. syringae pv tomato MM1065, multiplied less than 10-fold in leaves and had only a minimal effect on BG1, BG2, and BG3 mRNA accumulation, but it induced PAL mRNA accumulation. No accumulation of CHS mRNA was found with either ES4326 or MM1065. We also describe the cloning of a putative avirulence (avr) gene from the avirulent strain MM1065 that caused the virulent strain ES4326 to grow less well in leaves and to strongly elicit PAL but not BG1 and BG3 mRNA accumulation. These results suggest that the Arabidopsis PAL and BG genes may be activated by distinct signal transduction pathways and show that differences in plant gene induction by virulent and avirulent strains can be attributed to a cloned presumptive avr gene.